2008
DOI: 10.1016/j.molcel.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of SERCA1 Truncated Isoform in the Proapoptotic Calcium Transfer from ER to Mitochondria during ER Stress

Abstract: SUMMARY Among the new players at the endoplasmic reticulum (ER)-mitochondria interface regulating interorganelle calcium signaling, those specifically involved during ER stress are not known at present. We report here that the truncated variant of the sarcoendoplasmic reticulum Ca2+-ATPase 1 (S1T) amplifies ER stress through the PERK-eIF2α-ATF4-CHOP pathway. S1T, which is localized in the ER-mitochondria microdomains, determines ER Ca2+ depletion due to increased Ca2+ leak, an increased number of ER-mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
181
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 222 publications
(187 citation statements)
references
References 41 publications
6
181
0
Order By: Relevance
“…Earlier data have shown that ER Ca 2 þ depletion can be linked to the induction of the unfolded protein response (UPR). 18 However, our data revealed no induction of UPR in SDHA R554W cells (Supplementary Figure S3). These results may indicate that the increased cytosolic and mitochondrial agonist-evoked Ca 2 þ signals are largely linked to increased basal Ca 2 þ levels.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…Earlier data have shown that ER Ca 2 þ depletion can be linked to the induction of the unfolded protein response (UPR). 18 However, our data revealed no induction of UPR in SDHA R554W cells (Supplementary Figure S3). These results may indicate that the increased cytosolic and mitochondrial agonist-evoked Ca 2 þ signals are largely linked to increased basal Ca 2 þ levels.…”
Section: Resultsmentioning
confidence: 60%
“…The light signal was collected and calibrated into [Ca 2 þ ] values, as earlier described. 18 On the basis of the experimental traces, the maximum rates of ER Ca 2 þ uptake were measured from the first derivative of the ascending refilling phase obtained after CaCl 2 addition, and the maximum rates of ER Ca 2 þ leak were measured from the first derivative of the curve on addition of TBuBHQ using Origin 5 software. Fitting of the curve was performed using Microsoft Excel software.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations